Contrast-Induced Acute Kidney Injury in Patients on SGLT2 Inhibitors Undergoing Percutaneous Coronary Interventions: A Propensity-Matched Analysis - Hua, Rui; Ding, Ning; Guo, Hanqing; Wu, Yue; Yuan, Zuyi; Li, Ting (Frontiers in Cardiovascular Medicine, 2022)
Background Contrast-induced acute kidney injury (CI-AKI) is a common complication of patients undergoing percutaneous coronary intervention (PCI). Data regarding the influence of sodium-glucose cotransporter-2 (SGLT2) inhibitor on the CI-AKI incidence and renal outcomes of patients undergoing PCI are limited. This study aimed to examine the real-world risk of CI-AKI in SGLT2 inhibitor users undergoing PCI. Methods We used longitudinal data from the medical records of the First Affiliated Hospital of Xi'an Jiaotong University. We selected SGLT inhibitor users and nonusers [patients with type 2 diabetes (T2D) without SGLT2 inhibitor prescription] undergoing PCI. We determined CI-AKI by the ESUR (European Society of Urogenital Radiology, AKIESUR) and KDIGO definition (Kidney Disease: Improving Global Outcomes, AKIKDIGO). We performed 1:1 nearest-neighbor propensity matching and calculated unadjusted odds ratios (ORs) and adjusted ORs (aORs; accounting for covariates poorly balanced) for AKI in primary and sensitivity analyses. We compared the renal function indicators in users and nonusers at 24, 48, and 72 h post-PCI. Results We identified 242 SGLT2 inhibitor users and 242 nonusers in the cohort. The unadjusted ORs of CI-AKIESUR were 63% lower in users [OR: 0.37 (95% CI: 0.18–0.68); P = 0.01], which was unchanged [aOR: 0.37 (95% CI: 0.19–0.67); P < 0.01] post adjustment. These estimates did not qualitatively change across several sensitivity analyses. There was no significant difference in urea nitrogen, creatinine, and estimated glomerular filtration rate (eGFR) values between the two groups before PCI, and at 24 h, while the creatinine (48 and 72 h post-PCI) and CyC (24 and 48 h post-PCI) were significantly lower than those in the nonuser group (P < 0.05). Conclusion Our findings do not suggest an increased risk of CI-AKI associated with SGLT2 inhibitor use in patients with CAD and T2D undergoing PCI.